2005
DOI: 10.1111/j.1532-5415.2005.53111.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Potentially Harmful Informal Caregiver Behavior

Abstract: Potentially harmful caregiver behavior is more likely in spouse caregiving situations and when care recipients have greater needs for care and caregivers are more cognitively impaired, have more physical symptoms, and are at risk for clinical depression. This risk profile is similar to that for negative caregiver outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
239
1
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(253 citation statements)
references
References 16 publications
4
239
1
9
Order By: Relevance
“…HRQOL refers to the physical and mental aspects of health (Testa & Simonson, 1996), which directly correlates with the caregiver's health, and also impacts on the quality of care they provide to children with ASD and their resultant rehabilitation (Beach et al, 2005). Therefore, it is important to identify the predictors of HRQOL and provide effective interventions to caregivers of children with ASD.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…HRQOL refers to the physical and mental aspects of health (Testa & Simonson, 1996), which directly correlates with the caregiver's health, and also impacts on the quality of care they provide to children with ASD and their resultant rehabilitation (Beach et al, 2005). Therefore, it is important to identify the predictors of HRQOL and provide effective interventions to caregivers of children with ASD.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The difference between the two groups was statistically significant. In Mohammed Ali Heidari Gorji and Zinnatossadat Bouzar study, Beach SR and Schulz R study, 25 there were more mild and moderate depression among cancer caregivers. But in our study, equal prevalence of mild and severe depression among cancer caregivers was noted.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the caregiving role itself may further contribute to mistreatment. Risk factors for abusive behavior in caregivers include whether they are married to their partners with disabilities, caregiver physical symptoms, and caregivers' clinical depression (Beach et al, 2005). One study found that caregiver resentment strongly predicted potentially harmful behavior (Shaffer et al, 2007), while a related study concluded that the caregiver feeling like a victim and blaming the person with disabilities were salient predictive variables .…”
Section: Factors Associated With Mistreatmentmentioning
confidence: 99%